The Future of Economic Growth and Investment in Africa: A Bibliometric Analysis - Saleh, Husny Gibreel Musa; Hamidi, M. Luthfi; Musa, Hussein Gibreel; Emovwodo, Silas Oghenemaro; Garad, Askar (Universitas Proklamasi 45, 2024)
Economic growth increases a country’s real gross domestic product (GDP) over time. Investment is the expenditure on capital goods, such as machines, factories, and technology, that enhance the productive capacity of the economy. This paper aims to provide a comprehensive overview of the research trends and future directions in the field of economic growth and investment in Africa, based on a bibliometric analysis of the relevant literature. Using the Scopus database, we identified and analyzed 1,163 articles published between 2004 and 2023, This study employs a five-step methodology that consists of: (1) identifying keywords; (2) initializing search results; (3) including and excluding certain initial results items; (4) assembling initial data statistics; and (5) doing data analysis. The study findings revealed that the highest number of publications on economic growth and investment in Africa was in 2023 (166 articles), the top contributing affiliation was the University of South Africa, the leading influential country was South Africa and Social Sciences was the main source of contributions. Additionally, Odhiamb Nicholas M. topped the list of the top authors with high publications and 166 papers, while Simplice, Bekun, and Festus Victor held the top spot on the list of the most influential authors in terms of citations. Similarly, this study demonstrated that certain authors collaborate. This study identified four research clusters that could serve as a basis for future research expansion on economic growth and investment in Africa.